2023
DOI: 10.3389/fpubh.2023.1082325
|View full text |Cite
|
Sign up to set email alerts
|

“Burnout felt inevitable”: Experiences of university staff in educating the nursing and allied health workforce during the first COVID-19 waves

Abstract: IntroductionMaintaining progress in the face of looming burnout during the first 2 years of the COVID-19 pandemic was crucial for the health workforce, including those educating the next generation of health professionals. The experiences of students and healthcare practitioners have been explored to a greater degree than the experiences of university-based health professional educators.MethodsThis qualitative study examined the experiences of nursing and allied health academics at an Australian University dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Contributing factors included campus closures, limited preparation for transitioning to new learning modalities, ongoing planning for reopening, government mandates, and additional workloads and responsibilities [ 33 , 35 , 36 ]. Further, a recent Australian university study (2023) of Nursing and Allied Health staff reported increased workload and burnout, and identified several contributing factors, including managing distressed students, online teaching, stepping into leadership roles, staff shortages, and sourcing placements [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contributing factors included campus closures, limited preparation for transitioning to new learning modalities, ongoing planning for reopening, government mandates, and additional workloads and responsibilities [ 33 , 35 , 36 ]. Further, a recent Australian university study (2023) of Nursing and Allied Health staff reported increased workload and burnout, and identified several contributing factors, including managing distressed students, online teaching, stepping into leadership roles, staff shortages, and sourcing placements [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contributing factors included campus closures, limited preparation for transitioning to new learning modalities, ongoing planning for reopening, government mandates, and additional workloads and responsibilities [26,28,29]. Further, a recent Australian university study (2023) of Nursing and Allied Health staff reported increased workload and burnout, and identi ed several contributing factors, including managing distressed students, online teaching, stepping into leadership roles, staff shortages, and sourcing placements [30].…”
Section: Burnoutmentioning
confidence: 99%